A STUDY TO ASSESS THE IMPACT OF STRESS ON NECK PAIN IN AN ONLINE SESSION DURING COVID-19 PANDEMIC AND LOCKDOWN AMONG COLLEGE STUDENTS IN SHARDA UNIVERSITY - Chauhan, Tarun; E.K, Mr. Rajesh (International Journal For Research In Health Sciences And Nursing, 2022)
Background: Neck pain (NP), one of the most reported musculoskeletal disorders, is a major cause of illness and absence from university lessons among students. The COVID-19 pandemic affected higher education from university lessons among students. The COVID-19 pandemic affected higher education institutions worldwide. Academic studies shifted to online-learning, changing students’ habits and lifestyle. Data demonstrated that the pandemic and consequent lockdowns can affect people’s physical and mental well-being. Thus, the aim of this study is to evaluate the impact of COVID-19 pandemic and lockdown on the level of neck pain and shoulder pain among college students compared to the pre-epidemic period. Methods: A descriptive study was conducted in the form of an online questionnaire survey that included sociodemographic data, Neck Disability Index (NDI) and Perceived Stress Scale (PSS) Results: A total of 100 students were recruited. Among them the mean, standard deviation, median and the mean percentage of the stress level regarding neck pain among college students. The findings reveals that the majority of the college students, 49 (49%) had low stress level, 31 (31%) had moderate stress level and 20 (20%) had high stress regarding neck pain. The mean score for the stress level was 12.56 with a mean % of 44.12 whereas a median and standard deviation was 12 and 9.75 respectively. It can be concluded that higher the mean scores mean higher the stress level among the students. It indicates that any changes in stress level will affect the neck pain automatically among college students. Therefore, their online sessions will also get influenced due to neck pain in a given study. It is evidenced that these factors were influenced by stress level regarding their neck pain among college students during their online sessions. It is evidenced that any changes in stress level will also influenced more in the pain Intensity, lifting, concentration, work, sleeping and recreation activities as compared to other factors among college students during their online sessions in a given study. Conclusion: The purpose of the study was to investigate impact of covid-19 pandemic and lockdown on the level of neck pain and shoulder pain among college students. The statistical results have shown that about 49% had low stress levels, about 31% had moderate stress levels and 20% had high stress regarding neck and shoulder pain among the students. It can be concluded that the higher the mean scores value higher the stress level among the students. It is evidenced in other research that these factors were influenced by stress level regarding their neck pain among college students during their online sessions.